Multi-Wavelength Fluorescence in Image-Guided Surgery, Clinical Feasibility and Future Perspectives. (30th October 2020) - van Beurden, Florian; van Willigen, Danny M.; Vojnovic, Borivoj; van Oosterom, Matthias N.; Brouwer, Oscar R.; der Poel, Henk G. van; Kobayashi, Hisataka; van Leeuwen, Fijs W.B.; Buckle, Tessa
With the rise of fluorescence-guided surgery, it has become evident that different types of fluorescence signals can provide value in the surgical setting. Hereby a different range of targets have been pursued in a great variety of surgical indications. One of the future challenges lies in combining complementary fluorescent readouts during one and the same surgical procedure, so-called multi-wavelength fluorescence guidance. In this review we summarize the current clinical state-of-the-art in multi-wavelength fluorescence guidance, basic technical concepts, possible future extensions of existing clinical indications and impact that the technology can bring to clinical care.